Perancangan Sistem Informasi Pendaftaran Mahasiswa Baru Berbasis Mobile pada Universitas Islam As- Syafiiyah - Fauziah Fauziah (INSOLOGI: Jurnal Sains dan Teknologi, 2022)
At the time of admission of new students, the new student admissions committee experienced difficulties with incoming files and data. Prospective applicants also experience time, energy and financial difficulties during the registration process. Errors in the process of entering and processing data by administrators are also unavoidable because there is no application that can handle all processes into one system. Therefore, the presence of computer technology in the development of mobile-based information systems. greatly simplify and speed up registration for prospective students and data processing handled by the new student admissions committee at the As-Syafiiyah Islamic University. processing of registrant data and computerized data stored in the information system. registration of prospective students becomes easier and faster and can be accessed anywhere and anytime and makes it easier for the new student admissions committee to obtain complete data regarding the data of prospective new students who register. The output of this research is expected to make it easier for prospective new students to register for college entrance at the As-Syafi'iah Islamic University